Nanotechnology and agriculture in the tropical region: The perspective of the National Institute of Science and Technology in Brazil - Halley C. Oliveira; Adriano A. Melo; Leonardo F. Fraceto (Plant Nano Biology)
Agriculture in the tropics plays a fundamental role in producing food, feed and fiber for the world due to the diversity of production possibilities. However, despite its productive potential, there are many demands for technologies, whether for improving plant growth and development, monitoring field conditions, protecting plants from adverse climatic conditions, or pest control. Nanotechnology can assist in integrated crop management through different applications (e.g., nanosensors for pest monitoring and controlled-release nanoformulations of agrochemicals and biostimulants), thus bringing benefits to tropical agriculture. In this context, the creation of institutes with an interdisciplinary focus, such as the recently created National Institute of Science and Technology in Nanotechnology for Sustainable Agriculture in Brazil, can bring advantages through carrying out research and development, as well as transfer of technology for society, thus contributing to sustainable agriculture.